An inclusive ecotourism green finance funding model for South Africa - Mabe, Isang Tebogo (Graduate School of Business (GSB), 2025)
Climate change is occurring at a fast pace, and GHG emissions have already been locked in for future negative impacts. Marginalised communities bear the disproportionate burden of adapting to the negative impacts of climate change, due to unemployment and the lack of access to basic infrastructure. Addressing the negative impacts of climate change, and transitioning marginalised communities to climate change resilience, requires long-term sustainable commitments and community inclusion in industry projects. However, literature presumes a dichotomy between local community inclusion and the financial sustainability of the underlying project. South Africa has one of the most unequal societies in the world, due to labour income being vastly unequal among the various communities. In addition, the country is faced with a poor sovereign credit rating, which results in expensive traditional funding mechanisms, and a dearth of concessional green finance. Large sectors, such as energy and tourism, which contribute to significant GHG emissions, have not been investigated adequately for rapid decarbonisation in a sustainable local community inclusive approach. Consequently, this current research explores the incentives needed to stimulate the financial services sector to invest in sustainable green projects. A qualitative case study was conducted to determine how South Africa could be accelerated to a low carbon economy, through the lens of ecotourism or the energy sector. Interviews were conducted with experienced deal makers from 3 different financial services organisations involved in the energy and tourism sectors. The findings of this current research revealed that global actors with good sovereign credit ratings can provide largescale concessional green finance to de-risk projects, and create an enabling environment for local community inclusion. Additionally, cross sectorial collaborations enable a rapid decarbonisation of the ecotourism sector; however, energy demands far outstrip the available energy supply, making it challenging to decarbonise the energy sector. The findings also revealed a misalignment between global, national, and financial services actors to stimulate and incentivise investments in sustainable green projects, caused by competing objectives.